Multiple homodynamic eschistomelie in Glaphyrolytta viridipennis (Burmeister) (Coleoptera: Meloidae) - Faundez, Eduardo I.; Pineda, Cristian (My University, 2021)
A teratological case in a specimen of Glaphyrolytta viridipennis (Coleoptera: Meloidae) from Argentina is described. The case belongs to a multiple homodynamic eschistomelie in the right protarsus of the specimen. The possible causes of this malformation are discussed.
Keywords: meloinae; pyrotini; supernumerary; teratology